Effect of dietary supplementation of saccharicterpenin on growth, immunity and heat shock protein 70 content of juvenile turbot (Scophthalmus maximus) - Hao Tiantian; Wang Jiying; Li Baoshan; Zhang Derui; Sun Jianzhen; Sun Yongzhi; Zhang Limin (浙江大学学报. 农业与生命科学版, 2014)
Recently, intensive culture of Scophthalmus maximus has been seriously influenced by various diseases. To solve the problem, different kinds of antibiotics were incorporated in fish diets, which may produce potential drug-resistant pathogens and become a growing menace to aquatic animals as well as mankind. Therefore, it is urgent to develop new and safe additives in aquaculture.Saccharicterpenin is a bioactive compound derived from the plants of camellia seed, and its effective components are triterpenoid saponins and polysaccharides. Previous studies showed that saccharicterpenin could improve growth performance and immune function in freshwater fish. Thus, the aim of the study was examine the effects of dietary administration of saccharicterpen on growth performance, immunity and heat shock protein 70 (HSP-70) content of juvenile turbot, S. maximus (with initial body mass (55.0±0.2) g).Six isocaloric and isonitrogenous diets were formulated containing increasing levels (0, 25, 50, 75, 100, 200 mg/kg) of saccharicterpenin and named as D0, D25, D50, D75, D100, D200, respectively. Each diet was randomly assigned to triplicate groups of 30 juveniles. The experiment was conducted in plastic cylinder tanks in an indoor recirculated feeding system for 64 days. At the termination of the feeding trial, growth performance, serum and liver immunity and metabolic enzymes were determined. The remaining fishes were challenged intraperitoneally with Vibrio anguillarum.The results showed that fish fed with diets of D25, D50, and D75 showed significantly higher mass gain (MG), specific growth rate (SGR), protein efficiency ratio (PER), condition factor (CF), hepato-somatic index (HSI) and spleen-somatic index (SSI)(P<0.05), and obviously decreased feed conversion ratio (FCR)(P<0.05). However, viscero-somatic index (VSI) and survival rate (SR) revealed no noticeable difference among all treatments (P>0.05). Fish fed with diet of D50 showed the highest serum lysozyme activity. Superoxide dismutase (SOD) activity were significant enhanced in fish fed diets D75, D100 and D200 compared with other treatments (P<0.05). Nitric oxide content in serum was significant reduced with the increasing level of saccharicterpenin (P<0.05). HSP-70 contents in serum showed no significantly difference among all treatments (P>0.05). Aspartate transaminase (AST) of serum in D200 was significantly higher than the other groups (P<0.05), but alanine aminotransferase (ALT) showed no significantly difference (P>0.05). ALT and AST of liver significantly decreased with the increasing level of saccharicterpenin (P<0.05). There was no difference in total antioxidant capacity (T-AOC) in liver among all groups (P>0.05). Liver malondialdehyde (MDA) content in group D25 was significantly lower than that of D100(P<0.05), with no change among other groups (P>0.05). The challenge study showed that fish fed with diet of D50 presented lower cumulative mortality rate than other groups (P<0.05), and higher immune protective rate of 42.31% compared with those fed with diets of D25(19.23%) and D75(15.39%) after 48 hours, respectively.In conclusion, the addition of saccharicterpenin can improve the growth performance, immunity and disease resistance in S. maximus. Quadratic regression of SGR indicates that the optimal level of saccharicterpenin in diet for juvenile turbot is 74.58 mg/kg.